2000
DOI: 10.1023/a:1007697126844
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study we evaluated the smoking habits, beliefs and attitudes of nurse and medical students at the University of Siena and Florence, Italy. Students who entered the 1st year of school in 1998 were asked to complete a self-administered anonymous questionnaire. Two hundred medical students completed the questionnaire; they had a mean age (+/-SD) of 19.8+/-1.7 years and 68% were females. A total of 205 nurse respondents answered to the questionnaire; they had a mean age of 21.8+/-4.1 years and females were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…These figures were in line with studies of other university populations [ 52 , 53 ], although it is striking that nursing students had a higher frequency of smoking than students of other healthcare degrees (RR, 1.86; 95% CI (1.414–2.454); p < 0.001). This finding was already documented in studies conducted with healthcare students [ 6 , 54 ], as well as among healthcare professionals, with a higher prevalence of smoking among nurses than among physicians [ 55 ]. This also confirms that habits acquired in adolescence have a decisive influence on adult life and that they are perpetuated in many cases [ 11 ].…”
Section: Discussionsupporting
confidence: 61%
“…These figures were in line with studies of other university populations [ 52 , 53 ], although it is striking that nursing students had a higher frequency of smoking than students of other healthcare degrees (RR, 1.86; 95% CI (1.414–2.454); p < 0.001). This finding was already documented in studies conducted with healthcare students [ 6 , 54 ], as well as among healthcare professionals, with a higher prevalence of smoking among nurses than among physicians [ 55 ]. This also confirms that habits acquired in adolescence have a decisive influence on adult life and that they are perpetuated in many cases [ 11 ].…”
Section: Discussionsupporting
confidence: 61%
“…Regarding health risks according to curriculum, nursing students were more likely to smoke tobacco than the other healthcare students as already reported [ 52 ]. In our study, the prevalence in tobacco smoking among nursing students did no decrease in contrast with the findings reported by Ordas et al over a 10-year period (30.6% to 19.6%) [ 53 ].…”
Section: Discussionmentioning
confidence: 85%
“…Studies done in India 12 13 14 15 and in other countries 16 17 18 19 have revealed similar prevalence and pattern of substance abuse among medical students and other college students 20 . A study from India noted nearly 50 per cent of the undergraduate medical students reporting experiencing stress of variable severity, predisposing to substance abuse 13 .…”
Section: Resultsmentioning
confidence: 91%